Doses e épocas de aplicação de regulador de crescimento e doses de nitrogenio afetando cultivares de trigo. - Berti, Melissa (2006)
Trinexapac-ethyl is a growth reducer used in winter cereals that promote height plant reduction, preventing the lodging. With the aim of determine the rate and the time of ethyltrinexapac (Moddus) application in wheat cultivars of different lodging answers an experiment was established at the UEPG School Farm in Ponta Grossa, PR, in 2005, in a clay soil. The experimental design was complete randomized blocks, in a factorial design 2 x 2 x 6, with three repetitions for four wheat cultivars. The treatments consisted of two nitrogen rates (50 and 240 kg/ha), two times of trinexapac-ethyl application (between 1º and 2º knot and between 2º and 3º perceivable knot) and six trinexapac-ethyl rates (0; 31,2; 62,5; 93,7; 125,0 and 156,2 g/ha), applied in four wheat cultivars of different answers to the lodging (CD-104 - resistant), (Vanguarda - moderately resistant), (Supera - moderately susceptible) and (CEP-24 - susceptible). It evaluated agronomicals characteristics, diseases severity, yield components and yield. The nitrogen rate affected some plant characteristics and the yield for CEP-24. The application time of trinexapac-ethyl affect the yield of CD-104; the plant height that was lesser how much more delayed was the application in cultivars CEP-24 and CD-104; trinexapac-ethyl reduced the plants height of all the cultivars with changeable intensity with the port of the same ones. For all the cultivars the adjustment equation of the yield in relation to the trinexapac-ethyl rates was quadratic, occurring an increase of the yield with the increase of the reducer rate, until a changeable limit with the cultivar. However, for all cultivars occurred increase of the yield with the trinexapac-ethyl application. For the cultivar majority it had reduction of rust severity, head blight and foliar spots with the increase of the trinexapac-ethyl rate.